5x-6=3x+1

Simple and best practice solution for 5x-6=3x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-6=3x+1 equation:


Simplifying
5x + -6 = 3x + 1

Reorder the terms:
-6 + 5x = 3x + 1

Reorder the terms:
-6 + 5x = 1 + 3x

Solving
-6 + 5x = 1 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-6 + 5x + -3x = 1 + 3x + -3x

Combine like terms: 5x + -3x = 2x
-6 + 2x = 1 + 3x + -3x

Combine like terms: 3x + -3x = 0
-6 + 2x = 1 + 0
-6 + 2x = 1

Add '6' to each side of the equation.
-6 + 6 + 2x = 1 + 6

Combine like terms: -6 + 6 = 0
0 + 2x = 1 + 6
2x = 1 + 6

Combine like terms: 1 + 6 = 7
2x = 7

Divide each side by '2'.
x = 3.5

Simplifying
x = 3.5

See similar equations:

| x+4x+6=8 | | 2x+16=9x-40 | | 12x+16=5x+191 | | 12x+6y=70 | | a^2(a-4)=0 | | 12x=5x | | 4x+4y=30 | | 30T=1.75T^2 | | (250000*0.9/15)/12=x | | (250000-25000)/15/12=x | | 5x+20=13x-44 | | 17000/12=x | | 2x^2-4x+6= | | 250000/15=x | | 250000/15= | | 4x+5=-94-7x | | 88-3x=2x+23 | | 3p+2q=18 | | 4x+9=-13-7x | | y-(-7)=6(x-(-4)) | | 7-10x=23-24x | | y-(-7)=-6(x-(-7)) | | 10x+18=5x+128 | | 2x-3y+4=0 | | 12x-5y=0 | | 10x+8=5x+128 | | 89-2x=3x+24 | | 160-7x=20x+19 | | 5x+6=-84-10x | | y=3(5)+23 | | 4x+31=12x-49 | | 7y-12=9 |

Equations solver categories